Dynamic modelling methodology for an HTS energy converter using moving mesh. (2nd September 2021) - Li, Gengyao; Li, Chao; Xin, Ying; Hong, Wei; Li, Wenxin; Yang, Tianhui; Li, Bin
Abstract: Lots of high-temperature superconducting (HTS) devices which require current leads, slip rings or brushes have to face the challenges such as large heat load and complex structure. Recently, an HTS energy converter has been proposed, which can not only induce but also exploit persistent current in a closed HTS ring, realizing the conversion of mechanical energy—electromagnetic energy—mechanical energy wirelessly. In this work, a dynamic modelling method based on the H-formulation and moving mesh has been proposed to accurately simulate the electromagnetic performance of the HTS energy converter. The proposed modelling method can depict the induced current density inside the superconductor and magnetic field distribution, serving as a powerful tool to analyze the complex working principle of the HTS energy converter. The validity of the model has been verified by experimental results. Besides, effects of different parameters of the energy converter have been investigated in detail by our proposed model, to provide further insight into the design and applications of the device.